State Politics and Public Policy in Eastern Africa
XXVIII, 459 p. 34 illus.
Keywords: “A welcome focus on public policy and policy challenges from an extraordinarily diverse set of authors… It is rare to find such substantive breadth in a single volume.” —Catherine Boone, Professor, London School of Economics and Political Science, UK "Contributions from a variety of very accomplished researchers, primarily based in the region, tackle a series of important policy issues using a much-needed political lens.” —Anne Mette Kjær, Professor, Aarhus University, Denmark “This book is perhaps the most comprehensive coverage of politics and public policy in a single African region.” —Philip O. Nying’uro, Associate Professor, University of Nairobi, Kenya “This book is as insightful as it is needed… An important contribution on Eastern Africa with implications well beyond the region.” —Nic Cheeseman, Professor, University of Birmingham, UK This book analyses major themes in twenty-first-century east African politics. Predominantly authored by researchers and academics from the region, it examines recent political developments, public policy and governance across east and southern African countries. The book advocates for a regionally-focused comparative approach across Africa, arguing that it provides a greater level of analysis than a complete continental study. Adopting a multidisciplinary approach, it covers numerous topics relating to politics, public policy, state and nation-building in Africa. Filling an important void in current literature, the book will appeal to academics, practitioners, politicians and students of politics, public policy and governance. Chapter 16 and 20 are available open access under a Creative Commons Attribution 4.0 International License via link.springer.com. Gedion Onyango is Lecturer of Public Policy and Public Administration, University of Nairobi, Kenya.